When Is Foreignness an Asset or a Liability? Explaining the Performance Differential Between Foreign and Local Firms - Nachum, Lilach (Journal of Management, 2010)
I seek to make sense of the variety of performance differentials between foreign and local firms observed in international competition and to examine the circumstances that explain these varying outcomes. Toward this end, I develop a theoretical framework that allows for situations in which the costs and advantages that foreign firms have relative to local firms are stronger, weaker, or nonexisting. In this framework, the costs and advantages are measured relative to local firms, and the balance between them determines performance. Tests of the hypotheses on samples of local and foreign financial services firms in London show that affiliates experience the costs and advantages differentially in relation to local firms with varying characteristics. Affiliates enjoy superior advantages when compared with purely domestic local firms, but these differences disappear when affiliates are compared with local multinational enterprises (MNEs). Ownership levels significantly influence the strength of the costs and advantages, but different entry modes undertaken by MNEs have no discernible effect. These findings contribute to the understanding of the implications of foreignness in international competition and the reasons for it being an asset under certain circumstances and a liability under others. They illustrate the merits for practice of understanding the grounds for performance differentials between foreign and local firms, in that different reasons for this outcome require different strategic responses.